1998
DOI: 10.1046/j.1365-2133.1998.02499.x
|View full text |Cite
|
Sign up to set email alerts
|

Specialized keratin expression pattern in human ridged skin as an adaptation to high physical stress

Abstract: We have analysed the expression of keratins in the epidermis of normal human palm and sole skin (ridged skin) using immunohistochemistry and in situ hybridization. The epidermis of human ridged skin expresses a more complex pattern of keratins than thin skin, which is probably due to the greater stress that ridged skin has to withstand. In addition to keratin K9, we document specific expression patterns of keratins K6, K16 and K17 which are suggestive of regional adaptations of this epidermis to a high cell tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
110
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 41 publications
4
110
0
3
Order By: Relevance
“…3F). Regarding K6, which is normally expressed in hair follicle keratinocytes and in some basal and suprabasal keratinocytes in ridged skin (Swensson et al, 1998), we found expression in the companion layer of epidermal hair follicles without any difference between K5-Cre KO and control animals (Fig. 3G,H).…”
Section: Highly Efficient Reduction Of Plectin Levels By K5-controllementioning
confidence: 74%
“…3F). Regarding K6, which is normally expressed in hair follicle keratinocytes and in some basal and suprabasal keratinocytes in ridged skin (Swensson et al, 1998), we found expression in the companion layer of epidermal hair follicles without any difference between K5-Cre KO and control animals (Fig. 3G,H).…”
Section: Highly Efficient Reduction Of Plectin Levels By K5-controllementioning
confidence: 74%
“…8b). Collectively, this scenario, which resembles that of the complex epithelial keratin K1, K10, K9, and K2e expression pattern in suprabasal human plantar epidermis (35,36), suggests competitive, complex, and unique type I and type II hair keratin-pairing patterns. The same dynamics hold true for the potential pairing possibilities of matrix keratins and in particular cortex keratins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several other keratins are expressed in different parts of the epidermis and its appendages, in areas of distinct differentiation. These include the keratin K2e, which is widespread in the upper layers of the human epidermis (Collin et al, 1992), and K9, K6, K16, and K17, which are expressed in palmoplantar epidermis (Swensson et al, 1998). K6, K16, and K17 are also normally expressed in the hair follicles but are induced in suprabasal cells elsewhere during wound healing, tumorigenesis, and some hyperproliferative diseases, usually with a concomitant reduction in expression of K1 and K10 (Weiss et al, 1984;Wilson et al, 1994).…”
mentioning
confidence: 99%